Evaluation of the delivery of the family nurse partnership programme in Scotland during the COVID-19 pandemic - Lawrence Doi; Kathleen Morrison; Emmanuel Kwadwo Anago; Thomas Hughes (PLoS ONE, 2025)
Background The Family Nurse Partnership (FNP) is an intensive and structured person-centred home-visiting programme delivered by specially trained nurses, who offer support services to first-time young mothers. The COVID-19 pandemic prompted the quick adoption of telehealth within the FNP, as healthcare services moved rapidly to implement remote delivery systems in line with infection control measures. The aim of this study was 1) to understand the features of telehealth employed to deliver the FNP programme during COVID-19 in Scotland; 2) to examine how FNP nurses and clients responded to the delivery of FNP through telehealth; 3) to evaluate the challenges of delivering the FNP through telehealth during COVID-19 and its implications for future delivery of the programme. Methods The study employed a mixed-methods parallel design, where qualitative (one-to-one interviews and focus groups) and quantitative (survey) data were collected and analysed concurrently. Thirty-one family nurses took part in the focus groups and one-to-one interviews and a further 90 responded to the online survey. Fifteen FNP clients participated in one-to-one interviews. Interview data were analysed using thematic analysis and survey data were analysed by descriptive analysis. Results Family nurses combined both home visiting and remote delivery such as phone calls, SMS text messaging, emails, video calls to deliver the programme. Family nurses felt well equipped and supported to conduct their work remotely. Clients, particularly those who became isolated during COVID-19, overwhelmingly acknowledged this support and felt their family nurses provided stability, advice and care. However, both family nurses and clients found the rapid move to remote delivery challenging, because it affected both recruitment of clients with complex vulnerabilities to the programme and therapeutic relationship building. Nevertheless, 42% of family nurse respondents in the survey indicated that they would prefer mixed-mode delivery of face-to-face and telehealth as part of future FNP programme delivery. Conclusion Despite the challenges of delivering the programme remotely during COVID-19, telehealth has the potential to play a valuable role in post COVID-19 FNP programme delivery. A hybrid delivery approach could be appropriate in certain instances, for example clients not deemed to have complex vulnerabilities or those living in remote locations. Future studies could robustly examine the impact of the quality of modes of FNP delivery, for instance home visiting, telehealth and hybrid delivery and how these influence outcomes across different client groups. An economic evaluation of the value for money of different modes of delivery could also be insightful for decision makers.